2021
DOI: 10.1016/j.jshs.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Animal exercise studies in cardiovascular research: Current knowledge and optimal design—A position paper of the Committee on Cardiac Rehabilitation, Chinese Medical Doctors’ Association

Abstract: Highlights Standard procedures and appropriate assessment of exercise are proposed for the commonly used animal models related to chronic exercise (e.g., treadmill running, voluntary wheel running, swimming exercise, and resistance exercise) in cardiovascular research. Optimal design of animal exercise studies in cardiovascular research should consider the choice of exercise models, control of exercise protocols, exercise at different stages of disease, and other factors, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 184 publications
(306 reference statements)
0
29
0
Order By: Relevance
“…A growing number of systematic reviews and meta-analyses are published in recent years and used as sources of evidence in clinical and animal cardiology guidelines ( 2 4 ). However, concerns have been raised regarding the expertise, quality, and methodological standards of many systemic reviews ( 5 , 6 ).…”
Section: Highlights In General Cardiovascular Medicine: 2021mentioning
confidence: 99%
“…A growing number of systematic reviews and meta-analyses are published in recent years and used as sources of evidence in clinical and animal cardiology guidelines ( 2 4 ). However, concerns have been raised regarding the expertise, quality, and methodological standards of many systemic reviews ( 5 , 6 ).…”
Section: Highlights In General Cardiovascular Medicine: 2021mentioning
confidence: 99%
“…Endothelial dysfunction is a key feature of CAD and chronic heart failure (CHF). Numerous clinical trials showed that ET is an effective countermeasure for the injured endothelium in CAD and CHF patients [79]. The protective effects of 4 weeks of ET on endothelial dysfunction in patients with CAD (10 training patients and 9 control patients) were demonstrated by the improvement of Ach-induced vasoconstrictive responses and the increased mean peak flow velocity both in epicardial coronary vessels and in resistance vessels [80].…”
Section: The Beneficial Effects Of Exercise On Endothelial Dysfunction In Coronary Artery Disease and Chronic Heart Failurementioning
confidence: 99%
“… 1 Pathological myocardial remodeling is an early sign and a risk factor of heart failure, which may be caused by multiple stresses including hypertension and myocardial infarction. 2 , 3 , 4 , 5 However, the regulatory mechanisms of pathological cardiac remodeling and heart failure remain to be fully elucidated. 2 , 3 , 4 , 5 On the other hand, although increasingly advanced medical therapies can improve the symptoms of heart failure, it is still unable to prevent further development or reverse pathological progression.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 However, the regulatory mechanisms of pathological cardiac remodeling and heart failure remain to be fully elucidated. 2 , 3 , 4 , 5 On the other hand, although increasingly advanced medical therapies can improve the symptoms of heart failure, it is still unable to prevent further development or reverse pathological progression. 2 , 3 , 4 , 5 There is an urgent need of developing effective treatments of heart failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation